HUMAN RESOURCE MANAGEMENT IN IMPROVING THE QUALITY OF TEACHERS IN INDONESIAN ISLAMIC PRIMARY EDUCATION INSTITUTIONS - Sholeh, Makherus; Jannah, Raihanatul; Khairunnisa, Khairunnisa; Kholis, Nur; Tosson, Ghada (UIN Sunan Kalijaga Yogyakarta, 2021)
Human Resource Management (HRM) problems are familiar at all educational institutions, such as the Islamic Basic Educational Institution. This study aims to reveal and introduce the concept of HRM in improving the quality of teachers at the SDI (Islamic elementary education) Qurrota A'yun Tulungagung, Indonesia, to show the importance of HR in improving the quality of teachers in Islamic Primary Educational Institutions. Furthermore, this research involves ten informants, including a school principal, teachers, committees, parents, and community leaders. Subsequently, data were collected through in-person interviews (via telephone and online by WhatsApp messaging services), participant observation, and documentation. The results show the process of human resource management in improving the quality of teachers through planning, training, and evaluation. Firstly, the planning strategy is conducted through pre-service education or recruitment, while the training strategy is conducted by making on-the-job and off-the-job training programs. Lastly, Every week, semester, and year, the evaluation is completed, and rewards are given. In conclusion, the findings imply that human resource management has an important role in determining the quality of teachers.